Enantiomeric neolignans and sesquineolignans from Jatropha integerrima and their absolute configurations. Issue 16 (23rd January 2015) - Zhu, Jian-Yong; Cheng, Bao; Zheng, Yin-Jia; Dong, Zhen; Lin, Shu-Ling; Tang, Gui-Hua; Gu, Qiong; Yin, Sheng
Abstract : Two pairs of new sesquineolignan enantiomers, 1a/1b and2a/2b, one pair of new neolignan enantiomer, 4a/4b, and two new neolignans, 3a and5a, together with seven known analogues were isolated from the trunks of Jatropha integerrima . Abstract : Two pairs of new sesquineolignan enantiomers, (±)-jatrointelignans A and B (1a/1b and2a/2b ), one pair of new neolignan enantiomers, (±)-jatrointelignan D (4a/4b ), and two new neolignans, (+)-jatrointelignan C (3a ), and (+)-schisphenlignan I (5a ) together with seven known analogues (3b, 5b, 6a, 6b, 7a, 7b, and8 ) were isolated from the trunks of Jatropha integerrima . The structures were determined by combined spectroscopic and chemical methods, and their absolute configurations were elucidated by the circular dichroism (CD) method, in particular the configurations of the aryl glycerol-7′′, 8′′-yloxy moiety in1 and2 were determined via the Rh2 (OCOCF3 )4 -induced CD analysis. All compounds were examined for their inhibitory effects on nitric oxide (NO) production induced by lipopolysaccharide (LPS) in BV-2 microglial cells, and compounds5a, 6a, and4b exhibited pronounced inhibition on NO production with IC50 values in the range of 5.9–8.9 μM, being more active than the positive control, quercetin (IC50 = 17.0 μM).